Examining the mature interpersonal relationship status of first-year engineering students within residential learning communities - Waller, Brent, author; Strathe, Marlene, advisor; Gloeckner, Gene, committee member; Kuk, Linda, committee member; Tungate, Susan, committee member (Colorado State University. Libraries, 2015)
The purpose of this mixed-methods, sequential, explanatory study was to investigate the differences regarding the status of mature-interpersonal-relationship (MIR) development in first-year engineering students who elected to live within residential learning communities (RLCs) when compared to the status of MIR development in those first-year engineering students who lived within a traditional residential environment at a science, technology, engineering, and math (STEM) institution. A survey of 582 first-year engineering students at a STEM institution yielded quantitative results. Then, to explore the initial results in more depth, a follow-up study using two separate focus groups was completed with purposefully selected respondents. The follow-up qualitative phase attempted to provide logical connections to the findings from the original quantitative phase, which showed that students who live within RLCs have experiences that provide those students with opportunities for MIRs. In the quantitative phase, statistically significant results were limited to a difference by gender. The quantitative and qualitative findings from the two phases of the study are discussed, with reference to prior research. Implications and recommendations are provided.
Keywords: engineering students; psychosocial development; residence life; residential learning communities